The impact of board diversity on listed family firms in Singapore. - Nguyen, Khanh Linh. (2013)
This study was conducted to investigate the potential impacts of boardroom diversity, in terms of gender, tenure, education and ethnicity, on the performance of Singapore’s publicly listed family firms. Annual reports of all 370 family firms listed in the SGX Main Board in 2011 were studied for the extraction of data used in regression analyses. Relationships between Gender Diversity (represented by Percentage of female on board), Tenure Diversity (measured by coefficient of variation of tenure on board), Education Qualification Diversity (measured by Blau’s Index of Heterogeneity of Education Qualifications on board), Ethnicity Diversity (measured by Blau’s Index of Heterogeneity of Ethnicity on board) and firms’ performance (measured by Tobin’s Q) were each tested, with the control variables Total Assets, Leverage, Board Size and Market Capitalization. Results of our study indicate that Ethnicity Diversity is statistically significant to firms’ Tobin’s Q whilst there is no evidence of correlations between the other 3 diversity compositions and firms’ performance.